Dynamics of mono‐ and dual‐species biofilm formation and interactions between Staphylococcus aureus and Gram‐negative bacteria. Issue 4 (11th April 2017) - Makovcova, Jitka; Babak, Vladimir; Kulich, Pavel; Masek, Josef; Slany, Michal; Cincarova, Lenka
Summary: Microorganisms are not commonly found in the planktonic state but predominantly form dual‐ and multispecies biofilms in almost all natural environments. Bacteria in multispecies biofilms cooperate, compete or have neutral interactions according to the involved species. Here, the development of mono‐ and dual‐species biofilms formed by Staphylococcus aureus and other foodborne pathogens such as Salmonella enterica subsp. enterica serovar Enteritidis, potentially pathogenic Raoultella planticola and non‐pathogenic Escherichia coli over the course of 24, 48 and 72 h was studied. Biofilm formation was evaluated by the crystal violet assay (CV), enumeration of colony‐forming units (CFU cm −2 ) and visualization using confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM). In general, Gram‐negative bacterial species and S. aureus interacted in a competitive manner. The tested Gram‐negative bacteria grew better in mixed dual‐species biofilms than in their mono‐species biofilms as determined using the CV assay, CFU ml −2 enumeration, and CLSM and SEM visualization. In contrast, the growth of S. aureus biofilms was reduced when cultured in dual‐species biofilms. CLSM images revealed grape‐like clusters of S. aureus and monolayers of Gram‐negative bacteria in both mono‐ and dual‐species biofilms. S. aureus clusters in dual‐species biofilms were significantly smaller than clusters in S. aureus mono‐species biofilms. Abstract : Here, the development of mono‐ and dual‐species biofilms formed by Staphylococcus aureus and other food‐borne pathogens such as Salmonella enterica subsp. enterica serovar Enteritidis, potentially pathogenic Raoultella planticola and non‐pathogenic Escherichia coli over the course of 24, 48 and 72 h was studied. Biofilm formation was evaluated by the crystal violet assay (CV), enumeration of colony forming units (CFU cm −2 ) and visualization using confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM). The tested Gram‐negative bacteria grew better in mixed dual‐species biofilms than in their mono‐species biofilms and in contrast the growth of S. aureus biofilms was reduced when cultured in dual species biofilms, suggesting that tested strains interact in competitive manner.